Effect of growth medium and fertilizer types on the growth and yield of micropropagated ginger (Zingiber Officinale Rose. cv Tambunan) - Teoh, Yan Zhong (Universiti Malaysia Sabah, 2017)
This study was conducted at Faculty of Sustainable Agriculture (FSA), Universiti Malaysia Sabah (UMS), Sandakan, which is located at Mile 10, Jalan Sungai Batang, 90509 Sandakan Malaysia. This study was carried out under rain shelter number 4B to investigate the effect of growth medium and fertilizer types on the growth and yield of micropropagated ginger (Zingiber officinale Rose C>I Tambunan). The experimental design was Complete Randomized Design (CRD) using soil as a control treatment for media, Soil: Sand (3:1) and Sand: Cocopeat (1:1). Each medium was treated with pelleted chicken manure and foliar fertilizer. Each of the treatment was replicate 3 times and the observation was done for 24 weeks of planting. Parameters such as plant height (cm), number of leaves and number of tillers were recorded during observations while fresh weight of rhizomes (g), width of rhizomes (cm), length of rhizomes (cm) and dry weight of rhizomes (g) were determined after harvesting. The collected data were analysed using two-way analysis of variance (2-way ANOVA) F-test at 5% level and followed by Tukey Test at the 5% level for the parameters with significant difference through SPSS statistics version 21. Based on the results, there were significant differences between growth medium and fertilizer types for plant height (cm), number of leaves, number of tillers, width of rhizomes (cm) and length of rhizomes (cm) except for fresh weight of rhizomes (g), and dry weight of rhizomes (g). The results indicates that the application of pelleted chicken manure {Fl) on the growth and yield of micropropagated ginger was better compared to foliar fertilizer {F2). While growth medium, Ml (Soil) and M2 (Soil: Sand) were found to have better results compared to M3 (Sand: Cocopeat). Therefore, pelleted chicken manure was recommended for ginger planting. Meanwhile, Ml (Soil) and M2 (Soil: Sand) were recommended as planting medium for ginger.